Crocin Alleviates Pain Hyperalgesia in AIA Rats by Inhibiting the Spinal Wnt5a/β-Catenin Signaling Pathway and Glial Activation - Jin-Feng Wang; Hai-Jun Xu; Zhao-Long He; Qin Yin; Wei Cheng (Neural Plasticity)
At present, most of the drugs have little effect on the pathological process of rheumatoid arthritis (RA). Analgesia is an important measure in the treatment of RA and is also one of the criteria to determine the therapeutic effects of the disease. Some studies have found that crocin, a kind of Chinese medicine, can effectively alleviate pain sensitization in pain model rats, but the mechanism is not clear. Emerging evidence indicates that crocin may inhibit the metastasis of lung and liver cancer cells from the breast by inhibiting Wnt/β-catenin and the Wnt signaling pathway is closely related to RA. Wnt5a belongs to the Wnt protein family and was previously thought to be involved only in nonclassical Wnt signaling pathways. Recent studies have shown that Wnt5a has both stimulatory and inhibitory effects on the classical Wnt signaling pathway, and so, Wnt5a has attracted increasing attention. This study demonstrated that crocin significantly increased the mechanical thresholds of adjuvant-induced arthritis (AIA) rats, suggesting that crocin can alleviate neuropathic pain. Crocin significantly decreased the levels of pain-related factors and glial activation. Foxy5, activator of Wnt5a, inhibited the above effects of crocin in AIA rats. In addition, intrathecal injection of a Wnt5a inhibitor significantly decreased hyperalgesia in AIA rats. This research shows that crocin may alleviate neuropathic pain in AIA rats by inhibiting the expression of pain-related molecules through the Wnt5a/β-catenin pathway, elucidating the mechanism by which crocin relieves neuropathic pain and provides a new way of thinking for the treatment of AIA pain.